PENGUATAN KARAKTER RELIGIUS DALAM PEMBELAJARAN PAI : MENJAWAB TANTANGAN ETIKA DIGITAL GENERASI Z - Friska Alyana; Muhammad Akmansyah; Zahra Rahmatika (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT The study is motivated by the increasing challenges of digital ethics among students such as cyberbullying, hoax dissemination, low awareness of digital privacy, and moral degradation in social media use. This study aims to analyze Islamic Religious Education (PAI) learning practices in strengthening the religious digital ethics of Generation Z at SMA Negeri 1 Sekampung Udik. This study employed a descriptive qualitative approach using observation, interviews, and documentation techniques. The research participants consisted of PAI teachers, Rohis supervisors, and Generation Z students. The findings show that PAI learning practices are carried out through religious habituation, exemplary behavior, lectures, advice, integration of Islamic values in learning activities, and Rohis programs. Religious values such as discipline, responsibility, empathy, trustworthiness, and tabayyun shape students’ digital behavior to become wiser and more responsible. PAI learning also helps students develop self-regulation in using social media. This study indicates that PAI learning has an important contribution in shaping the religious digital ethics of Generation Z through character strengthening and digital behavior control. ABSTRAK Penelitian ini didasari oleh meningkatnya tantangan etika digital pada peserta didik seperti cyberbullying, penyebaran hoaks, rendahnya kesadaran menjaga privasi digital, serta menurunnya nilai moral dalam penggunaan media sosial. Penelitian ini bertujuan untuk menganalisis praktik pembelajaran Pendidikan Agama Islam (PAI) dalam penguatan etika digital religius Generasi Z di SMA Negeri 1 Sekampung Udik. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Informan penelitian terdiri dari guru PAI, pembina Rohis, dan peserta didik Generasi Z. Hasil penelitian menunjukkan bahwa praktik pembelajaran PAI dilakukan melalui pembiasaan religius, keteladanan, ceramah, pemberian nasihat, integrasi nilai Islam dalam pembelajaran, serta kegiatan Rohis. Nilai religius seperti disiplin, tanggung jawab, empati, amanah, dan tabayyun mampu membentuk perilaku digital peserta didik menjadi lebih bijak dan bertanggung jawab. Pembelajaran PAI juga membantu peserta didik mengembangkan self-regulation dalam menggunakan media sosial. Penelitian ini menunjukkan bahwa pembelajaran PAI memiliki kontribusi penting dalam membentuk etika digital religius Generasi Z melalui penguatan karakter dan pengendalian perilaku digital.